The Role of Microfabric and Laminae on Pore Structure and Gas Transport Pathways of Marine Shales from Sichuan Basin, China. (21st July 2020) - Shu, Yi; Xu, Shang; Yang, Feng; Shu, Zhiguo; Peng, Pan; Huang, Senxin; Zhen, He
Abstract : This study investigated the effects of microfabric and laminae on the pore structure and gas transport pathways of the Silurian Longmaxi shales from Sichuan Basin. 23 shale samples with varied lithofacies were comprehensively investigated by mineralogy, organic geochemistry, pycnometry, and low-pressure nitrogen adsorption analysis. The fabric and laminae of these samples were identified using petrographic microscope and scanning electron microscopy. Permeabilities were measured using the nonsteady-state method on both perpendicular and parallel to bedding shales. The effective pore diameter controlling gas transport was estimated from gas slippage factors obtained in permeability measurements. These values were also compared to those calculated using the Winland equation. Siliceous shales studied are faintly laminated to nonlaminated and have larger porosity and specific surface area. Argillaceous/siliceous mixed shales are well laminated, whereas argillaceous shales contain many oriented clay flakes along the lamination. Both porosity and surface area are positively correlated with TOC content. Unlike most conventional reservoirs, there is a negative correlation between porosity and permeability values of the samples studied. Permeabilities parallel to bedding, ranging from 0.4 to 76.6 μ D, are in control of the oriented clay flakes and silty microlaminae. Permeability anisotropy values of the shales vary between 1.3 and 49.8. Samples rich in oriented clay flakes and microlaminated fabric have relatively larger permeability and permeability anisotropy values. The effective transport pore diameters derived from gas slippage measurements are slightly lower than those calculated from the Winland equation. However, both methods have shown that the effective transport pore diameters of argillaceous shales (averaging 552 nm) are significantly higher than siliceous shales (averaging 198 nm), which underlines the control of microfabric, rather than porosity, on gas transport pathways of the shales studied.